The Relationship between Epstein-Barr Virus Infections with Papillary Thyroid Cancer: A Review of Studies in Iran - Daneshvar, Ali; Shafee, Ali; Shirazi, Amin Ostovar; Lotfi, Maryam; Karbasi, Zahra; Yarahmadi, Amir (International Journal of Psychosocial Rehabilitation, 2026)
Background and aim: Papillary thyroid cancer (PTC), It is the most common thyroid cancer and one of the most common cancers of the glands. The causes of this cancer are varied but more recently, the role of viral infections has been suggested. EBV is one of the most important viruses that it is related to different types of malignancies. In this review article, The Relationship between EBV and Papillary Thyroid Cancer in studies conducted in Iran has been investigated. Methods: This review study was performed in the period of last 10 years (2010-2020). All related articles with Keywords: EBV, EPSTEIN-BARR VIRUS, Papillary thyroid cancer, PTC, follicular thyroid cancer AND FTC searched in research engines: Google Scholar, science Direct, PubMed and Sid (for article in Persian) Entered the study. Search results showed that in this time period of 10 years, 3 related studies conducted in Iran. In this article we have summarized the results of these three studies. Result: All three studies reviewed, emphasized that Epstein-Barr virus is associated with papillary thyroid cancer and it can be considered a risk factor for this cancer. So monitoring patients with latent EBV, for papillary thyroid cancer can be very important. Conclusion: We found correlation between EBV and thyroid cancer in based on the current evidence. But more studies are needed to demonstrate the relationship between the virus and Papillary thyroid cancer. Future studies are warranted to reveal the significance of EBV in thyroid tumor developments.